1996
DOI: 10.1021/ie950771p
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Characterization of Slurries in an Autoclave Reactor at Elevated Temperature

Abstract: An ultrasonic technique was developed to measure the concentration of solids in an autoclave reactor. Preliminary measurements were conducted on slurries consisting of molten paraffin wax, glass beads, and nitrogen bubbles at 189 °C. The data show that the velocity and attenuation of the sound are well-defined functions of the solid and gas concentrations in the molten wax. The results suggest possibilities for directly measuring solids concentration during operation of a three-phase slurry reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…(6) into Eq. (5), the amplitude ratio is found to be dependent on the gas holdup only and is expressed as (7) or (8) In addition, Waristo [19] proposed a similar result as follows:…”
Section: The Principle Of the Ultrasonic Methods For Gas Holdup Measurmentioning
confidence: 93%
See 1 more Smart Citation
“…(6) into Eq. (5), the amplitude ratio is found to be dependent on the gas holdup only and is expressed as (7) or (8) In addition, Waristo [19] proposed a similar result as follows:…”
Section: The Principle Of the Ultrasonic Methods For Gas Holdup Measurmentioning
confidence: 93%
“…In the actual measurement, the pulsed ultrasound method is typically used to extract the useful information of the fluid such that it avoids the interference of standing waves in continuous ultrasound measurement [7]. The dispersed phase concentration plays an important role in the amplitude of the transmission ultrasound [8], and the ultrasonic attenuation changed with regularity when the gas flow rate increased [9]. Rahiman et al introduced a mathematical model to explain the influence of a single gas bubble on ultrasound propagation, concluding that the ultrasonic attenuation increased with increases in the bubble diameter [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ultrasound can be used to characterize complex slurries, such as those at Hanford (Clark and Martin 1994). Other groups have used ultrasound to monitor slurries at elevated temperatures (Soong et al 1996) and ultrasonic piezoelectric transducers are now available that can operate at temperatures as high as 950ºC (Patel et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Both the amplitude ratio and the travel time were affected by the solids concentration. Soong et al (1996) performed similar measurements in three phase slurries of molten paraffin wax, nitrogen bubbles, and glass beads. In this study, the bubble size was also about 5 mm.…”
Section: Measurement Techniques In Liquid-liquid Dispersion Andmentioning
confidence: 97%